2019
DOI: 10.1016/j.heliyon.2019.e01167
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA and the perspectives of miR-302

Abstract: MiRNAs are naturally occurring, small, non-coding RNA molecules that post-transcriptionally regulate the expression of a large number of genes involved in various biological processes, either through mRNA degradation or through translation inhibition. MiRNAs play important roles in many aspects of physiology and pathology throughout the body, particularly in cancer, which have made miRNAs attractive tools and targets for translational research. The types of non-coding RNAs, biogenesis of miRNAs, circulating mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 128 publications
0
7
0
Order By: Relevance
“…Consequently, miR-302a might be a biologically and analytically attractive biomarker for ASD with a severe symptomatic biomarker. Moreover, consistent findings have shown that the miR-302 family is critical in stem cell pluripotency and renewal, and somatic cell DNA demethylation [ 20 , 21 , 22 ]. miR-135b-5p was another miRNA that was flagged in our study as being expressed at significantly higher levels in individuals who expressed severe symptoms versus mild ones.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Consequently, miR-302a might be a biologically and analytically attractive biomarker for ASD with a severe symptomatic biomarker. Moreover, consistent findings have shown that the miR-302 family is critical in stem cell pluripotency and renewal, and somatic cell DNA demethylation [ 20 , 21 , 22 ]. miR-135b-5p was another miRNA that was flagged in our study as being expressed at significantly higher levels in individuals who expressed severe symptoms versus mild ones.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly we observed that the miR-302 family (hsa-miR-302a-5p, hsa-miR-302c-3p, hsa-miR-302a-3p, hsa-miR-302d-3p, hsa-miR-302b-3p, hsa-miR-302c-5p and hsa-miR-302b-5p) were expressed at significantly high levels in individuals that expressed severe ASD symptoms in comparison to those that expressed mild symptoms. Previous findings have shown that the miR-302 family is crucial in stem cell pluripotency and renewal and somatic cell DNA demethylation [ 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…miR‐302e is a member of the miR‐302 cluster family, which also contains miR‐302a, miR‐302b, miR‐302c, and miR‐302d (Guo et al, ). Except for miR‐302e, other members in this family have been extensively studied and considered as tumor suppressors in many human cancers (Chen, Chen, & Ying, ; Li, Huo, Pan, Wang, & Ma, ). In our data, miR‐302e was observed to be significantly down‐regulated in NSCLC and identified as a tumor growth inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐302 family members are intronic and embryonic stem (ES) cell‐specific miRNAs. They play important roles in many biological processes; these processes include the pluripotency, self‐renewal, and reprogramming of ES cells, as well as antitumor activities (Chen et al, 2019). A study investigated the roles of the miR‐302 cluster in HT‐29 colorectal cancer cells, and it found that the miR‐302 cluster can modulate oncogenic properties through inhibition of proliferation, angiogenesis, and invasion, as well as reversal of the epithelial‐to‐mesenchymal transition (Maadi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%